2012
DOI: 10.1002/0471142905.hg0612s75
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Rare Homozygous Mutations from Studies of Consanguineous Pedigrees

Abstract: The unmasking of recessive mutations by virtue of biparental inheritance of the same ancestral haplotype on which they reside (autozygosity) has provided human geneticists with one of their most powerful tools in unraveling the genetic basis of autosomal recessive disorders. This has historically been achieved by tracking the blocks of homozygosity as surrogates of autozygosity using polymorphic microsatellite markers. Mapping the entire set of autozygous blocks per individual (autozygome) at high resolution b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 33 publications
2
71
0
Order By: Relevance
“…In the case of MGAT2, we have previously shown that this is probably due to the poor documentation of dysmorphology in the metabolic literature. 13,16,23,24 Similarly, we note that the craniosynostosis we observed in the setting of mild global developmental delay in the two siblings with MAN2B1 mutation was initially considered a novel phenotype for the same reason. Although craniosynostosis is not listed as a known feature of mannosidosis in OMIM or review articles, we found, in retrospect, that craniosynostosis had indeed been described, albeit very rarely.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In the case of MGAT2, we have previously shown that this is probably due to the poor documentation of dysmorphology in the metabolic literature. 13,16,23,24 Similarly, we note that the craniosynostosis we observed in the setting of mild global developmental delay in the two siblings with MAN2B1 mutation was initially considered a novel phenotype for the same reason. Although craniosynostosis is not listed as a known feature of mannosidosis in OMIM or review articles, we found, in retrospect, that craniosynostosis had indeed been described, albeit very rarely.…”
Section: Discussionmentioning
confidence: 70%
“…12 When multiple affected members were available, their shared autozygome was determined. 13 Whole-exome and whole-genome sequencing Exome capture was performed using a TruSeq Exome Enrichment kit (Illumina, San Diego, CA) following the manufacturer's protocol. Samples were prepared as an Illumina sequencing library; in the second step, the sequencing libraries were enriched for the desired target using the Illumina Exome Enrichment protocol.…”
Section: Autozygome Analysismentioning
confidence: 99%
“…Determination of the entire set of autozygous intervals per genome (autozygome) and autozygosity mapping were carried out as described previously. 16,17 Briefly, we used algorithms (AutoSNPa and HomozygosityMapper) that consider regions of homozygosity (ROH) >2 Mb in size as surrogates of autozygosity.…”
Section: Genotyping and Autozygome Analysismentioning
confidence: 99%
“…Although the two siblings in the other branch lacked any additional BBS feature, one of these two siblings had an infant with BBS in the course of the study. As a result, and based on our experience of rare cases in which BBS presents as nonsyndromic RP (Abu Safieh et al 2010, 2012, we enrolled this family in this study. However, autozygome analysis and exome sequencing confirmed that the apparent clinical heterogeneity in this family was, in fact, the result of independent segregation of two different diseases: RP secondary to RP1 mutation and BBS due to BBS1 mutation.…”
Section: Genome Research 237mentioning
confidence: 99%